Does physician pay affect procedure choice and patient health? Evidence from medicaid C-section use - Diane Alexander (Federal Reserve Bank of Chicago, 2017)
I investigate the relationship between physician pay, C-section use, and infant health, using vital statistics data and newly collected data on Medicaid payments to physicians. First, I confirm past results - when Medicaid pays doctors relatively more for C-sections, they perform them more often. I bolster the causal interpretation of this result by showing that salaried doctors do not respond to this pay differential, and by using a much larger sample of states and years. Second, unlike past work, I look at how changing physician pay affects infant health outcomes. I find that increased Csection use is associated with fewer infant deaths for births likely covered by Medicaid, suggesting that C-section rates may be too low for some groups. Taken together, these findings suggest that policies aimed at decreasing costs by lowering procedure use may have adverse health consequences, especially for low-income patients.
Keywords: I11; I13; I18; 330